2016
DOI: 10.3390/ijerph13121238
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic and Immigrant Paradoxes in U.S. Breast Cancer Mortality: Impact of Neighborhood Poverty and Hispanic Density

Abstract: To test the Hispanic and Immigrant Paradoxes—i.e., survival advantages despite a worse risk factor profile—and the modifying role of neighborhood context, we examined associations between patient ethnicity, birthplace, neighborhood Hispanic density and neighborhood poverty among 166,254 female breast cancer patients diagnosed 1995–2009 in Texas, U.S. Of all, 79.9% were non-Hispanic White, 15.8% Hispanic U.S.-born, and 4.2% Hispanic foreign-born. We imputed birthplace for the 60.7% of Hispanics missing birthpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 55 publications
(106 reference statements)
3
15
0
Order By: Relevance
“…Latinas living in neighborhoods with lower SES faced worse survival from both causes in both states. This finding is consistent with a large body of literature demonstrating worse survival among patients with cancer who are living in neighborhoods with low SES, regardless of how nSES is measured …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Latinas living in neighborhoods with lower SES faced worse survival from both causes in both states. This finding is consistent with a large body of literature demonstrating worse survival among patients with cancer who are living in neighborhoods with low SES, regardless of how nSES is measured …”
Section: Discussionsupporting
confidence: 91%
“…Differences in methodology, including nativity imputation methods, may explain these discrepancies. Consistent with prior research, we also demonstrated that foreign‐born Latinas were more likely to live in ethnic enclaves and neighborhoods with low SES …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…50 The remaining studies all utilized measures of ethnic composition, but no clear pattern of findings emerged. One study reported a positive association, 53 but two reported no association with breast cancer mortality. 15,54 A study of women with cervical cancer reported no association of Hispanic ethnic density with mortality.…”
Section: Resultsmentioning
confidence: 99%